Serum Vitamin D Levels in Autoimmune and Non-Autoimmune Hypothyroidism: A Retrospective Study from Jordan - Alqurieny, Hadeel; Al-Slehat, Mohammad; Bdour, Karam; Lail, Roa'a Abedel Razaq Abu; Abu-Salih, Abdel Qader; Aldebei, Zaid Iyad Mohammad; Al-Bdour, Mohammad; Shimi, Rula Al; Quraan, Asmaa; Yasin, Abdel Razaq Al; Ayyash, Fadi (Avicenna Journal of Medicine, 2025)
Vitamin D is a steroid hormone primarily produced in the skin. In Jordan, vitamin D deficiency is widespread among the population. This study aims to compare serum vitamin D levels between patients with autoimmune and non-autoimmune hypothyroidism.A retrospective observational study was conducted at the Jordanian Royal Medical Services in Jordan from January 2023 to November 2024. Data were gathered from the patient's medical records, including age, gender, vitamin D level, thyroid-stimulating hormone (TSH) value, free thyroxine (FT4) level, anti-thyroid peroxidase, and anti-thyroglobulin levels.A total of 150 patients were included, aged 5 to 76 years, with a mean age of 39.2 years. The mean vitamin D level was 17.9 ng/mL, indicating widespread deficiency. There was no significant difference in vitamin D levels between patients with autoimmune and non-autoimmune hypothyroidism (p = 0.860), suggesting that vitamin D levels are independent of autoimmune hypothyroidism status. Additionally, there was no significant relationship between vitamin D levels and TSH (ρ = −0.119, p = 0.148) or FT4 (ρ = 0.128, p = 0.123). Age showed a modest negative correlation with TSH levels (ρ = −0.067, p = 0.416) and a positive but nonsignificant correlation with FT4 levels (ρ = 0.024, p = 0.775).Serum vitamin D levels do not significantly differ between patients with autoimmune and non-autoimmune hypothyroidism, nor do they correlate with TSH levels. Further studies are needed to evaluate vitamin D status in these patient groups.
Keywords: autoimmune hypothyroidism; non-autoimmune hypothyroidism; 25-hydroxyvitaminD; FT4